2013
DOI: 10.1111/1365-2745.12167
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity promotes persistence following severe events: physiological and morphological responses of seagrass to flooding

Abstract: Summary 1.Severe events such as floods or cyclones can have large ecological effects on the structure and functioning of ecosystems. The capacity of an ecosystem to adapt to, or absorb, the effects of a severe event depends on the severity and longevity of the event and the tolerance of the species present.2. Seagrasses exhibit phenotypic plasticity at the plant to meadow scale through a variety of physiological and morphological acclimations to light stress to enhance photosynthetic capacity. These acclimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 65 publications
(79 reference statements)
1
62
0
Order By: Relevance
“…These areas may function as seed sources and allow the recovery of lost areas (Calleja et al 2017). When considering seagrass resistance and recovery, it is generally agreed that the greater the trait variability, the more likely the system is to survive periods of stress (Maxwell et al 2014). A main aspect of such studies is to understand how local factors are compromising and, in some cases, contributing to the resilience of seagrass ecosystems (Unsworth et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These areas may function as seed sources and allow the recovery of lost areas (Calleja et al 2017). When considering seagrass resistance and recovery, it is generally agreed that the greater the trait variability, the more likely the system is to survive periods of stress (Maxwell et al 2014). A main aspect of such studies is to understand how local factors are compromising and, in some cases, contributing to the resilience of seagrass ecosystems (Unsworth et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A main aspect of such studies is to understand how local factors are compromising and, in some cases, contributing to the resilience of seagrass ecosystems (Unsworth et al 2015). Although this study does not focus on analysing the causes, there is evidence in the literature suggesting that exposure to certain environmental stresses may enable individuals or communities to adapt to drivers and improve their resistance (Maxwell et al 2014, Calleja et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…A coincident benthic photo was acquired before each core harvest; these photos were geo-referenced and analysed for seagrass percentage cover and species composition as per the method in the following section. Whilst above and below-ground biomass are reasonably well correlated, exploratory work suggested that predicting below-ground biomass from above-ground estimates would not be appropriate using the same simple linear modelling approach, which is expected given demonstrated variability in seagrass phenology in Moreton Bay (Maxwell et al 2014). Thus we modelled above-ground biomass only, and all references to biomass refer to above-ground biomass.…”
Section: Model Input Datamentioning
confidence: 99%
“…Seagrass in Moreton Bay displays high phenotypic plasticity (Maxwell et al 2014), with morpho -9 Fig. 4.…”
Section: Uncertainty In Biomass Estimatesmentioning
confidence: 99%
See 1 more Smart Citation